Case Report: Necrotizing fasciitis caused by Staphylococcus aureus positive for a new sequence variant of exfoliative toxin E - Sabat, Artur J.; Wouthuyzen-Bakker, Marjan; Rondags, Angelique; Hughes, Laura; Akkerboom, Viktoria; Koutsopetra, Olga; Friedrich, Alexander W.; Bathoorn, Erik (Frontiers in Genetics, 2022)
Objectives: Necrotizing fasciitis (NF) caused by S. aureus is a rare, aggressive and rapidly progressing superficial fascia infection with a high mortality rate. The aim of this study was to identify virulence-related genes from a complete genome sequence of a methicillin-susceptible S. aureus (MSSA) isolate recovered from a monomicrobial case of NF. Materials and methods: The MSSA isolate UMCG579 was cultured from a pus collection from the subcutis of a patient with NF. The genome of isolate UMCG579 was sequenced using MinION (Oxford Nanopore) and MiSeq (illumina) platforms. Results: The genome of the UMCG579 isolate was composed of a 2,741,379 bp chromosome and did not harbor any plasmids. Virulence factor profiling identified multiple pore-forming toxin genes in the UMCG579 chromosome, including the Panton-Valentine leukocidin (PVL) genes, and none of the superantigen genes. The UMCG579 isolate harbored a new sequence variant of the recently described ete gene encoding exfoliative toxin (type E). A search in the GenBank database revealed that the new sequence variant (ete2) was exclusively found among isolates (n = 115) belonging to MLST CC152. While the majority of S. aureus ete-positive isolates were recovered from animal sources, S. aureus ete2-positive isolates originated from human carriers and human infections. Comparative genome analysis revealed that the ete2 gene was located on a 8777 bp genomic island. Conclusion: The combination of two heterogeneously distributed potent toxins, ETE2 and PVL, is likely to enhance the pathogenic ability of S. aureus isolates. Since anti-virulence therapies for the treatment of S. aureus infections continue to be explored, the understanding of specific pathogenetic mechanisms may have an important prophylactic and therapeutic value. Nevertheless, the exact contribution of ETE sequence variants to S. aureus virulence in NF infections must be determined.